A Survey of Diabetes Mellitus in a Sample of Children below 15 Years Attending Child Welfare Hospital - Sulaf A. Hussain (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: Determine the age and gender distribution of children who experience diabetes mellitus (DM) under the age of 15 years and the presence of some associated factors that might be a predisposing factor for the disease including obesity. Methodology: A cross-sectional study was conducted at diabetic clinic in Children Welfare Teaching Hospital in Baghdad City during 2006. The study sample included diabetic children less than 15 years of age. Data were taken from the patients’ record and by direct interview with the patients’ parents. Information included demographic data, as well as past history of the patient and his/her family relative to diabetes and other immune diseases. Results: Data analysis showed that there was an equal distribution of patients among the three age groups (I-5, 6-10-, and 11-15 years) in a rate of 33% for each. Females had higher incidence rate (660/o) than males. Onset of the disease was mostly at age group I-3 years (32%) followed by age group 4-6 years (30%). IIistory of viral illness was present in 24% of patients and a positive family history of DM was found in 23% of them, and a family history of autoimmune disease was positive in 13% of cases. Body weight at the first visit to the clinic was mainly below the 50th percentile (42% within the 25th percentile) and only 4% of patients had a body weight within the 75th percentile. Recommendations: Health education about the disease and provision of health centers those are easily accessible for early diagnosis and treatment and uninerrupted insulin supply.